2015
DOI: 10.1111/all.12776
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and targeting of Siglec‐FhighCD11clow eosinophils to the airway in a murine model of asthma

Abstract: Eosinophil recruitment in asthma is a multistep process, involving both trans-endothelial migration to the lung interstitium and trans-epithelial migration into the airways. While the trans-endothelial step is well studied, trans-epithelial recruitment is less understood. To contrast eosinophil recruitment between these two compartments, we employed a murine kinetics model of asthma. Eosinophils were phenotyped by multicolor flow cytometry in digested lung tissue and bronchoalveolar lavage (BAL) simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 13 publications
8
76
1
Order By: Relevance
“…In most homeostatic adult tissues, the numbers of resident eosinophils range from very limited to non‐existent. For instance, resident eosinophils in the healthy adult mouse lung average 1.5% of the total CD45 + hematopoietic cell population, although the turnover rate and functional significance of such resident populations is not well understood. Eosinophil numbers increase significantly in the following types of tissue microenvironments: (1) at homeostatic sites where epithelial cell turnover and stem cell activity are high (small intestine, endometrial lining of the uterus, bone marrow, thymus); (2) during developmental/morphogenetic events (ductal differentiation of mammary glands, development of Peyer's patches, postnatal lung development, beige fat biogenesis); (3) during processes of normal injury repair; (4) in diseases involving extensive tissue remodeling (helminthic parasite infections, acute lung injury (oxygen stress), fibrosis, cancers, allergic diseases of the gut, skin, and airway, and non‐atopic diseases with a significant remodeling component (eosinophilic esophagitis, chronic rhinosinusitis, AERD)); and (5) endocrinopathies.…”
Section: Tissue Microenvironments Associated With Increased Eosinophimentioning
confidence: 99%
See 1 more Smart Citation
“…In most homeostatic adult tissues, the numbers of resident eosinophils range from very limited to non‐existent. For instance, resident eosinophils in the healthy adult mouse lung average 1.5% of the total CD45 + hematopoietic cell population, although the turnover rate and functional significance of such resident populations is not well understood. Eosinophil numbers increase significantly in the following types of tissue microenvironments: (1) at homeostatic sites where epithelial cell turnover and stem cell activity are high (small intestine, endometrial lining of the uterus, bone marrow, thymus); (2) during developmental/morphogenetic events (ductal differentiation of mammary glands, development of Peyer's patches, postnatal lung development, beige fat biogenesis); (3) during processes of normal injury repair; (4) in diseases involving extensive tissue remodeling (helminthic parasite infections, acute lung injury (oxygen stress), fibrosis, cancers, allergic diseases of the gut, skin, and airway, and non‐atopic diseases with a significant remodeling component (eosinophilic esophagitis, chronic rhinosinusitis, AERD)); and (5) endocrinopathies.…”
Section: Tissue Microenvironments Associated With Increased Eosinophimentioning
confidence: 99%
“…Eosinophils are found in very low numbers at steady state but those numbers significantly increase during development and disease. Moreover, developmental and disease eosinophils are phenotypically distinct from true resident cells in homeostasis . Analogous to this, the homeostatic intestine undergoes active epithelial turnover, which also happens at a much slower rate in the steady state lung.…”
Section: Shaping Eosinophil Phenotype and Morphology In Heterogeneousmentioning
confidence: 99%
“…Some recent very interesting articles studied mouse lung tissue eosinophils and partly also human lung tissue eosinophils (87, 88). Abdala Valencia and colleagues reported that, after antigen challenge, mouse lung tissue eosinophils shifted from a surface phenotype with intermediate expression of Siglec-F and no or very low α X integrin (CD11c) to a Siglec-F-high/CD11c-low phenotype, and that BAL eosinophils were of the latter phenotype (87).…”
Section: A Model For Eosinophil Activation States In the Circulation mentioning
confidence: 99%
“…Abdala Valencia and colleagues reported that, after antigen challenge, mouse lung tissue eosinophils shifted from a surface phenotype with intermediate expression of Siglec-F and no or very low α X integrin (CD11c) to a Siglec-F-high/CD11c-low phenotype, and that BAL eosinophils were of the latter phenotype (87). Mesnil and others found that mouse steady-state pulmonary resident eosinophils were IL-5-independent and expressed an intermediate level of Siglec-F (in consistency with the first tissue phenotype in the Abdala Valencia publication), high L-selectin (CD62L), and low CD101 (immunoglobulin superfamily member 2) (88).…”
Section: A Model For Eosinophil Activation States In the Circulation mentioning
confidence: 99%
“…Lung hEos represent an exception and rather resemble resting blood eosinophils. Indeed, both blood and lung eosinophils have a ring-shaped nucleus (as is the case for mammary hEos as well), express CD62L, display only intermediate levels of Siglec-F, and are negative for CD11c (8, 10, 17, 36, 37) (Figure 1). In mouse eosinophils, such characteristics, especially the presence of a ring-shaped nucleus, are considered a sign of cell immaturity (38, 39), suggesting that pulmonary hEos retain an immature phenotype when spreading into the lungs.…”
Section: Morphological and Phenotypic Features Of Heosmentioning
confidence: 89%